2008
DOI: 10.1292/jvms.70.1337
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Diabetes Mellitus Accompanied by Exocrine Pancreatic Insufficiency in a Dog

Abstract: ABSTRACT. A 6-month-old male crossbred dog weighing 0.78 kg was presented with acute bilateral immature cataracts, intermittent diarrhea and growth retardation. The clinical manifestations and laboratory findings were suggestive of concurrent juvenile diabetes mellitus (DM) and exocrine pancreatic insufficiency (EPI). Moreover, the DM was associated with a decreased level of serum insulin-like growth factor I. Histological examination revealed a markedly lower number of pancreatic islets and acinar cells. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Juvenile DM is a rare condition in dogs and has been reported anecdotally in a small number of dogs [1,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. To the authors knowledge, this is the largest collection of dogs with JDM reported in the literature.…”
Section: Plos Onementioning
confidence: 99%
“…Juvenile DM is a rare condition in dogs and has been reported anecdotally in a small number of dogs [1,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. To the authors knowledge, this is the largest collection of dogs with JDM reported in the literature.…”
Section: Plos Onementioning
confidence: 99%
“…Overt diabetes during diestrus in bitches may be due to higher levels of progesterone causing glucose intolerance (Kim et al, 2012). Juvenile diabetes, a form of insulin dependent diabetes mellitus has also been reported in canines with particular prevalence in golden retrievers, German shepherd and keeshonds (Kang et al, 2008).…”
Section: Classification Of Diabetes Mellitusmentioning
confidence: 99%
“…Generally, canine diabetes mellitus is clinically diagnosed in dogs with 4-18 years of age, the median age at diagnosis being 7-9 years [37,[44][45][46]. Swedish study [37] UK study [44] North America study [ Juvenile onset of the disease is an uncommon event and it has been recorded in dogs with less than 12 months of age [47][48][49]. Several studies concluded that females are prone to diabetes (more than 70% of diagnosed cases) [37].…”
Section: Type 1 Diabetes Mellitus In Dogmentioning
confidence: 99%
“…Lees damaged islets may present mitotic figures (fig 2). When insulitis do not occur, histological examination reveals only a lower number of pancreatic islets [49]. Amyloid deposition is characteristic for cat diabetes.…”
Section: Lesions Of Diabetes Mellitus In Dog and Catsmentioning
confidence: 99%